Kajian Kualitas Beras Sosoh Dari Berbagai Macam Ukuran Daya Mesin Penggiling - I B Werdi Putra; Yohanes Setiyo; I Gusti Ngurah Apriadi Aviantara (Jurnal BETA (Biosistem dan Teknik Pertanian), 2020)
Rice is a staple food for the people of Indonesia. Even though Indonesia is an agrarian country, Indonesia currently imports rice. In producing rice from rice there are obstacles. One of the main obstacles is post-harvest handling of rice with high yield loss during post-harvest. The amount of post-harvest loss occurs because most farmers still use traditional methods or the handling is not good and right. The purpose of this study was to determine the relationship between the capacity of the grinding machine and the quality of sosoh rice produced by the mill and to know the quality comparison of various types of grinding machine capacity. The research was carried out in the area of ??Wanasari Village, Tabanan-Bali to find out the quality of sosoh rice in the region. Head Rice is broken rice grains, both healthy and defective, which have a size greater than or equal to 6/10 part of the average length size of whole rice grains that can pass through the surface of the indented plate basin with a requirement of 4.2 mm hole size. Rice husk is a protective cover from rice grains which is separated from seeds during the grinding process. In the grinding process, there is rice which remains the husk which is caused by the power / rpm of the grinding machine which is too low because the friction force produced by the engine is not sufficient for the overall release of rice husk